Cognitive reasoning : a formal approach - Gergely, Tamas , 1952-; Anshakov, Oleg M. [ (Oleg Matveevich)] (Cognitive technologies, 2010)
Dealing with uncertainty, moving from ignorance to knowledge, is the focus of cognitive processes. Understanding these processes and modelling, designing, and building artificial cognitive systems have been challenging research problems.